OP0200 Circulating, Auto-Reactive B Cells Specific for Citrullinated Antigens in Patients with Rheumatoid Arthritis Display An Activated, Proliferative Phenotype. (15th July 2016) - Kristyanto, H.; Kerkman, P.F.; van der Voort, E.; Spits, H.; Baeten, D.; Huizinga, T.W.; Toes, R.E.; Scherer, H.U.
Abstract : Background: Rheumatoid arthritis (RA) is characterized by the formation of autoantibodies against citrullinated antigens (CA). Intriguingly, depletion of CD20+ B cells leads to significant clinical improvement in the majority of patients, despite the persistence of high titer autoantibodies. This indicates that the CD20+ B cell compartment, potentially more than the autoantibodies themselves, contributes to the pathogenesis and/or chronicity of RA. Auto-reactive B cells within this compartment could be the main drivers of this effect, but evidence for this hypothesis is lacking. We recently developed the technology to visualize and characterize CA-specific B cells in patients and demonstrated that a large proportion has a CD20+ memory phenotype 1 . Objectives: To study the phenotype of CA-specific B cells in comparison to tetanus-toxoid (TT)-specific B cells in peripheral blood of individual patients. Methods: Differentially labeled CA and their arginine control variants were used as tetramers to identify CA-specific B cells in peripheral blood of patients with RA. TT-specific B cells were identified in the same samples using differentially labeled TT. Both antigen-specific cell populations were enumerated and phenotypically characterized by flow cytometry. Results: CA-specific B cells and TT-specific B cells were detected in peripheral blood in comparable frequency (median 0.012% vs. 0.014%). Both CA- and TT-specific B cells displayed mainly markers of class-switched memory B cells. Intriguingly, CA-specific memory B cells showed remarkable overexpression of co-stimulatory molecules and markers of active proliferation. Conclusions: This is the first phenotypic analysis of auto-reactive, CA-specific memory B cells in comparison to recall antigen-specific memory B cells in individual patients with RA. CA-specific memory B cells overexpress co-stimulatory molecules and proliferation markers, indicative of an active immune response against CA in these patients. These data support the hypothesis that CA-specific memory B cells contribute to RA pathogenesis and fuel efforts for their antigen-specific depletion. References: Kerkman PF et al. Identification and characterisation of citrullinated antigen-specific B cells in peripheral blood of patients with rheumatoid arthritis. Ann Rheum Dis. 2015 Jun 1. doi: 10.1136/annrheumdis-2014-207182. Acknowledgement: Supported by grants from the Dutch Arthritis Foundation, The Netherlands Organization for Scientific Research and the Innovative Medicines Initiative funded project BeTheCure. Disclosure of Interest: H. Kristyanto: None declared, P. Kerkman: None declared, E. van der Voort: None declared, H. Spits Employee of: AIMM Therapeutics, D. Baeten: None declared, T. Huizinga: None declared, R. Toes: None declared, H. Scherer: None declared